Towards a global understanding of vegetation-climate dynamics at multiple timescales - Linscheid, Nora (2021)
Funding Information: Acknowledgements. This paper has been realized within the Earth System Data Lab project funded by the European Space Agency. The authors acknowledge Lina Fürst for initiation of the preliminary study laying the foundation for this project. The authors acknowledge support from Ulrich Weber for data management and preprocessing. Lina M. Estupinan-Suarez acknowledges the support of the DAAD and its Graduate School Scholarship Programme (57395813). Nora Linscheid acknowledges the support of the TUM Graduate School. Lina M. Estupinan-Suarez and Nora Linscheid acknowledge the continuous support of the International Max Planck Research School for Global Biogeochemical Cycles. Felix Cre-mer acknowledges the support of the German Research Foundation project HyperSense (grant no. TH 1435/4-1). Publisher Copyright: © Author(s) 2020. Copyright: Copyright 2020 Elsevier B.V., All rights reserved.